Patrimônio cultural, políticas urbanas e de preservação: os casos de Diamantina e Tiradentes - Leticia Mourao Cerqueira (2006)
Urban issues are imperative in Brazil, especially concerning that 80% of the population is concentrated in urban areas. Cities had mostly been growing without urban planning, in order to promote urban development. They face many sort of serious problems such as those related to urban-cultural heritage preservation. Frequently, cultural heritage goods are located in the historical urban cores. The preservation of those central areas had manly occurred as a result of cities stagnation. However, in consequence of urban growth high rates there have been changes. Urban growth interferes on natural and historical landscape and environment and it impacts cultural heritage goods and its surroundings. In order to investigate these issues, this dissertation focused on the links between urbana policies and cultural heritage preservation policies. It explores the foundations of these policies as well as their possible connection to strengthen their effectiveness. This research examines urban and cultural policies regulation instruments (basically laws), legal documents as well as academic production, with the objective to verify those policies conceptions and instruments, and also their impacts on municipalities contexts. The City Statute (The Urban Development Federal Law) and the local Master Plan are analyzed, concerning their potentials to promote preservation of the historical cities. As the master plans establish urbanism rules and parameters they have been considered the main base to protect cultural heritage. Two historical cities were chosen as comparative case studies Diamantina and Tiradentes. The field work focused on government interventions, mainly those performed by IPHAN (the federal agency responsible for heritage protection) and their effects on urban planning. In both cities, cultural heritage preservation is a central issue, as it attracts tourism flow and activities and impact local economies generating work and income. Urban management involves inter-governmental relations among sub-national and national levels in order to protect cultural heritage. However, this work points out many difficulties in these relations that increases preservation costs and brings up obstacles to policies implementation and effectiveness. Cities analysis performed by this work supported by documental research on IPHANs documents and data made it possible to approach policies tools and instruments. The research also addresses the relevant links between urban and preservation policies. It contributes to understanding of the processes related to urban-cultural heritage preservation on Diamantina and Tiradentes, identifying main obstacles and challenges. This sort of knowledge is important to the formulation of urban policies engaged with heritage preservation and conservation.